The Influence of Celebrity Source’s Credibility’s Dimensions and Congruence on Behavioral Intention, with Attitude towards Brand as the Mediator: The Case of BTS as Tokopedia’s Brand Ambassador and Millennial Customers - Melissa Melissa; Geofanny Nathalia (iBuss Management, 2021)
Indonesia's e-commerce market grows by around 17% anually, and is one of the fastest and largest in the world. Tokopedia is one of highly demanded e-commerce companies in Indonesia has partnered up with BTS as its brand ambassador in 2019. Recognizing the limited research that studies on the effectiveness of endorser credibility toward behavioral intention, especially in the e-commerce field, this research aimed to analyse the the influence of celebrity source credibility’s dimensions and congruence on behavioral intention, with attitude toward brand as the mediator of BTS as Tokopedia’s brand ambassador with millennial customers. This research uses simple random sampling through online questionnaires. The research is also limited to 130 respondents who belong to the millennial generations, those who are 21-40 years old, in Indonesia. The data are analysed with multiple linear regression and Sobel test with path analysis in IBM SPSS 26. The result of this research found that attractiveness is fully mediated and trustworthiness is partially mediated by attitude towards brand in influencing behavioral intention. Nevertheless, this research result found that expertise and congruence do not significantly influence behavioral intention and attitude towards brand.Keywords:Celebrity Endorsement, Attractiveness, Trustworthiness, Expertise, The Congruence, Behavioral Intention.